Rapid Hemophilia A Molecular Diagnosis by a Simple DNA Sequencing Procedure: Identification of 14 Novel Mutations - Vidal, Francisco; Farssac, Elisenda; Altisent, Carme; Puig, Lluís; Gallardo, Dominique (Thrombosis and Haemostasis, 2001)
We here describe a simple, efficient DNA sequencing procedure for hemophilia A molecular diagnosis. In severe patients we first test for the presence of factor VIII gene intron 22 inversion using a recently described single-tube PCR method. In moderate, mild, or inversion-negative severe patients we systematically sequence the promoter, all exons and splice junctions of factor VIII gene. Specially designed primers allow amplification of 23 PCR products under the same salt conditions and thermocycling parameters. The whole sequencing procedure, from blood extraction to mutation identification, can be readily done within 42 h when using regular instruments or in just 14 h when using a high-throughput sequencer. Thus, this is a versatile and cost-effective strategy with little hands-on time requirements. Since its implementation we have identified mutations in 45/46 hemophilia A patients, 14 of which are novel. Once the genetic defect has been identified, accurate genetic counseling is then easily performed.
Keywords: Factor VIII; hemophilia A; mutations; automated DNA sequencing; F8c